Astronomical Aspects of the Early Determination of Subuh - Sheabi Astiya; Gandhung Fajar Panjalu; Andi Sitti Mariyam (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
Differences are a natural thing, but differences of opinion in determining the initial time of dawn need to be reconsidered, because this concerns the human obligation to worship. Therefore, this research was conducted with the aim of discussing various kinds of differences regarding the initial determination of dawn and finding the right conclusions. The research method used is qualitative, by applying library research that uses various kinds of literature to become basic research guidelines. The results of this study indicate that at -20o the light cannot be seen because it is still too far below the horizon, so if at that point the light is seen then it is necessary to ask whether the light comes from dawn or is the light of the zodiac or what is known as the kadzib dawn (dawn false).